Research Progress on the Preparation, Properties and Potential Applications of Cellulose-Based Hydrogels - Avnir, Abu; Fischer, Raz; Carroll, Ann (Journal of Functional Materials and Applied Engineering, 2024)
Cellulose-based hydrogels are three-dimensional networks locked by physical ties or covalent bonds, marrying cellulose’s renewable, cell-friendly backbone with the classic hydrogel signature—water weight that can top 99 %. This paper first introduces cellulose dissolution systems and methods (alkali/urea systems, inorganic salt systems, and ionic liquid systems). Starting from solutions of cellulose and its derivatives, we revisit physical and chemical routes to these networks, then chart how they now serve biomedicine, environmental clean-ups and stretchable circuits—praising their robust mechanics, cytocompatibility, green disposal and stimulus-smart behaviour. The survey offers a roadmap for turning abundant cellulose into high-value, next-generation materials.